2013
DOI: 10.2105/ajph.2012.301049
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Agonist Treatments and Heroin Overdose Deaths in Baltimore, Maryland, 1995–2009

Abstract: Increased access to opioid agonist treatment was associated with a reduction in heroin overdose deaths. Implementing policies that support evidence-based medication treatment of opiate dependence may decrease heroin overdose deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
163
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(166 citation statements)
references
References 41 publications
3
163
0
Order By: Relevance
“…Both buprenorphine and methadone treatment are associated with reduced overdose risk and improved maternal and fetal outcomes in pregnancy (19,44,51,72). Despite strong evidence supporting the use of buprenorphine and methadone, fewer than 1 million Americans are receiving these treatments (87).…”
Section: Tertiary Preventionmentioning
confidence: 99%
“…Both buprenorphine and methadone treatment are associated with reduced overdose risk and improved maternal and fetal outcomes in pregnancy (19,44,51,72). Despite strong evidence supporting the use of buprenorphine and methadone, fewer than 1 million Americans are receiving these treatments (87).…”
Section: Tertiary Preventionmentioning
confidence: 99%
“…In patients undergoing treatment for opioid use disorders, methadone therapy is associated with several improved outcomes, including retention in drug treatment as well as reduced opioid use, and some observational studies have observed reductions in allcause mortality and risk of death from overdose (Esteban et al, 2003;Gibson et al, 2008;Huang & Lee, 2013;Langendam, van Brussel, Coutinho, & van Ameijden, 2001;Mattick, Breen, Kimber, & Davoli, 2009;Perry et al, 2013;Schwartz et al, 2013). On the basis of its effectiveness, the World Health Organization added methadone to its list of essential medicines in 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Even under ideal conditions, PDMPrelated reductions in OA deaths appear to be similar to those reported for laws and policies that increase access to the overdose reversal medication naloxone, for example, and lower than those associated with increased access to medical cannabis [2,17,18]. They are far lower than those associated with opioid agonist and partial agonist treatment [19]. These interventions also have the benefit of reducing mortality related to all opioids, not just OAssomething that has not been shown to be true for PDMPs.…”
mentioning
confidence: 58%